p53 mRNA and p53 Protein Structures Have Evolved Independently to Interact with MDM2 - Karakostis, Konstantinos; Ponnuswamy, Anand; Fusée, Leïla T S; Bailly, Xavier; Laguerre, Laurent; Worall, Erin; Vojtesek, Borek; Nylander, Karin; Fåhraeus, Robin (Molecular biology and evolution, 2016)
The p53 tumor suppressor and its key regulator MDM2 play essential roles in development, ageing, cancer, and cellular stress responses in mammals. Following DNA damage, MDM2 interacts with p53 mRNA in an ATM kinase-dependent fashion and stimulates p53 synthesis, whereas under normal conditions, MDM2 targets the p53 protein for degradation. The peptide- and RNA motifs that interact with MDM2 are encoded by the same conserved BOX-I sequence, but how these interactions have evolved is unknown. Here, we show that a temperature-sensitive structure in the invertebrate Ciona intestinalis (Ci) p53 mRNA controls its interaction with MDM2. We also show that a nonconserved flanking region of Ci-BOX-I domain prevents the p53-MDM2 protein-protein interaction. These results indicate that the temperature-regulated p53 mRNA-MDM2 interaction evolved to become kinase regulated in the mammalian DNA damage response. The data also suggest that the negative regulation of p53 by MDM2 via protein-protein interaction evolved in vertebrates following changes in the BOX-I flanking sequence.
Keywords: RRM proteiny; Proto-Oncogene Proteins c-mdm2; DNA Primers; protein–RNA interactions; messenger RNA; Protein Binding; MDM2; RNA structures; RNA, Messenger; apoptóza; Base Sequence; Apoptosis; Protein Structure, Tertiary; poškození DNA; vztahy mezi strukturou a aktivitou; terciární struktura proteinů; Structure-Activity Relationship; vazba proteinů; nádorový supresorový protein p53; nádorové buněčné linie; p53; RNA Recognition Motif Proteins; invertebrate.; DNA primery; Animals; Cell Line, Tumor; DNA Damage; protoonkogenní proteiny c-mdm2; sekvence nukleotidů; Ciona intestinalis; Tumor Suppressor Protein p53; zvířata